2018
DOI: 10.1002/pd.5196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of umbilical cord occlusion methods: Radiofrequency ablation versus laser photocoagulation

Abstract: Despite clear technical advantages of RFA compared with laser, we found that RFA appeared to be associated with increased risk of post-procedure fetal demise. Further studies should be conducted to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
4
20
1
Order By: Relevance
“…However, while Yinon et al found similar rates of preterm delivery following RFA and BC, 12 we found a significantly higher rate of preterm delivery following both BC and laser, compared to RFA, and fewer adverse perinatal outcomes following RFA. Unlike one meta‐analysis that reported higher rates of PPROM with BC, 21 we found no such difference in PPROM rates with any method, in accordance with other studies 11,12 . Our results also differ from a recent study comparing RFA with laser, which found a similar GA at delivery following both techniques, but worse outcomes following RFA, specifically a higher rate of co‐twin demise 11 .…”
Section: Discussionsupporting
confidence: 77%
“…However, while Yinon et al found similar rates of preterm delivery following RFA and BC, 12 we found a significantly higher rate of preterm delivery following both BC and laser, compared to RFA, and fewer adverse perinatal outcomes following RFA. Unlike one meta‐analysis that reported higher rates of PPROM with BC, 21 we found no such difference in PPROM rates with any method, in accordance with other studies 11,12 . Our results also differ from a recent study comparing RFA with laser, which found a similar GA at delivery following both techniques, but worse outcomes following RFA, specifically a higher rate of co‐twin demise 11 .…”
Section: Discussionsupporting
confidence: 77%
“…Criteria for using RFA at our center have been previously described [22, 23]. Routine indications for RFA primarily include TRAP sequence and obligate lethal discordant anomalies.…”
Section: Methodsmentioning
confidence: 99%
“…RFA, using a 17-gauge needle to ablate tissues within 2 cm diameter, is relatively simple and effective, obtaining a lower incidence of preterm premature rupture of membranes (PPROM) and preterm delivery [5,8,13]. Other advantages that make RFA the preferred technique involve situations where there is difficulty in terms of access to other surgical treatments, including oligohydramnios of the target twin, proximity of twin cord insertion sites, anterior placenta or earlier gestational age [14].…”
Section: Introductionmentioning
confidence: 99%
“…The primary indications for RFA are TRAPs and other lethal foetal anomalies [14]. After RFA, the overall survival rate of the co-twin in TRAPs is determined to be at 75.0-92% [8][9][10][15][16][17][18][19], but it varies in other anomalies, ranging 33-92.3% [8,13,15].…”
Section: Introductionmentioning
confidence: 99%